2007
DOI: 10.1007/s11295-007-0097-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci for wood quality and growth across eight full-sib coastal Douglas-fir families

Abstract: Typical linkage and quantitative trait locus (QTL) analyses in forest trees have been conducted in single pedigrees with sex-averaged linkage maps. The results of a QTL analysis for wood quality and growth traits of coastal Douglas-fir using eight full-sib families, each consisting of 40 progeny, replicated on four sites are presented. The resulting map of segregating genetic markers consisted of 120 amplified fragment length polymorphism (AFLP) loci distributed across 19 linkage groups. The wood quality trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 39 publications
5
31
0
1
Order By: Relevance
“…These were located on maps using software MapChart (Voorrips 2002). The proportion of phenotypic variation explained by the trait-marker association was estimated by the formula (Ukrainetz et al 2008): where R 2 is the coefficient of determination for the proportion of variation explained by the QTL; SS G is the sum of squares of the genotype (QTL); and SS Total is the total sum of squares. The phenotypic effect of the QTL-associated marker was estimated by the equation (Broman 2001): where PE (%):…”
Section: Methodsmentioning
confidence: 99%
“…These were located on maps using software MapChart (Voorrips 2002). The proportion of phenotypic variation explained by the trait-marker association was estimated by the formula (Ukrainetz et al 2008): where R 2 is the coefficient of determination for the proportion of variation explained by the QTL; SS G is the sum of squares of the genotype (QTL); and SS Total is the total sum of squares. The phenotypic effect of the QTL-associated marker was estimated by the equation (Broman 2001): where PE (%):…”
Section: Methodsmentioning
confidence: 99%
“…The MFA of at least 18 Arabidopsis stems from VND7 and the pom2-4 mutant in VND7 was measured using an x-ray diffraction technique (Ukrainetz et al, 2008). The bottom 3 cm of mature, senesced plant stems was used for analysis.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Nonetheless, MAS has been proposed as a potential strategy to identify top individuals at early age within particular elite full-sib families of very large size by tracking a few large effect QTLs Johnson et al 2000;O'Malley et al 1994). QTL mapping studies in forest trees with increased statistical power have shown that a larger number of QTL with relatively small and variable effects across backgrounds and environments typically underlie complex traits (Dillen et al 2008;Ukrainetz et al 2008;Freeman et al 2011). Breeding for several traits simultaneously by QTL-based MAS in such a scenario is practically precluded while the potential for MAS-based on the cumulative effect of several marker-trait associations found in candidate genes could be realized (see Section "Gene discovery and association genetics").…”
Section: Molecular Breedingmentioning
confidence: 99%